Nilai Karakter Religius pada Novel Bumi Cinta Karya Habiburrahman El Shirazy - Hatibul Umam; Nurul Yakin; Muhammad Fahrurrozi (Action Research Journal, 2024)
This study aims to analyze the religious character values ​​contained in the Bumi Cinta novel by Habiburrahman El Shirazy, a writer. Religious values consist of faith, morals, and sharia. This study uses a qualitative approach with the content analysis method. Data sources consist of primary and secondary data. Data collection is carried out using library techniques and content analysis. Data analysis techniques use content analysis. Data validity checking is carried out by increasing perseverance and reference materials. From the results of the analysis carried out by the researcher, it can be concluded that religious character values ​​include faith, morals, and sharia. Faith consists of trust and faith in Allah SWT. Morals consist of morals towards fellow human beings, including respecting fellow human beings, tolerance with other people of different religions, being responsible, and morals towards parents. Sharia consists of being prohibited from touching those who are not mahram and maintaining views. The author's socio-historical background influences how his works are. The author is a religious individual who was raised in a religious environment, thus producing literary works, especially novels, which are closely linked to Islamic values